Development of Transitional Care Model for the Elderly with Chronic Illness - ธีรานุตร, อัมพรพรรณ; เหลืองอมรเลิศ, สุจิตรา; ศรีธัญรัตน์, วรรณภา; ทัศนิยม, นิตย์; จิตพิมลมาศ, สุทธิพันธ์ (วารสารพยาบาลศาสตร์และสุขภาพ, 2012)
Participatory action research was adopted in thisstudy to develop a transitional care service modelfor elderly individuals with chronic illnesses receivingcare in a tertiary care hospital of northeastern Thailand.The studyûs participants included registered nurses whoworked in the unit, an interdisciplinary health care team,elderly patients who had chronic illnesses, and theirfamilies, as well as personnel in other related healthunits.Analyses of the study site confirmed that theexisting transitional care services didnût adhere to theestablished guidelines.  The existing services includeddischarge planning and patient and family educationregarding self-care activities to be practiced at home.Nurses were responsible for setting up the dischargeplan using information gathered from patients and theirmedical records, however, patientsû problems and thenursing care plans were not communicated between thenurses responsible for the patientsû discharge and thenurses working in other shifts.  In addition, there wereseveral issues related to discharging and continuing careat home.  The discharge plan had not been used asa guide to prepare patients and their families before being discharged from the hospital.  The documentationrelated to hospital discharge and continuing care wereincomplete, and as a result, not supportive of carecontinuation.  Furthermore, nurses often perceived thatdischarge planning had not been an ongoing process,and was burdening and difficult to manage.  Cooperationbetween the hospital and local primary care units(PCUs) was lacking and often lead to ineffective patientdischarge.  Patients and their families were not providedenough information and necessary skills and patientswere unable to go home even when their doctors hadgiven their consent to do so.  As a result, they feltunconfident in terms of performing self-care activitiesat home and were dissatisfied with the service theyreceived during their hospital stay.The research team designed several interventionsto address these problems by collaboratively analyzingthe existing problems and circumstances as well asexploring various options for the solution.  The nursesûthought and work systems had been reorganized toadhere to a process of team nursing care, so that nursesworking in the unit were able to provide continuingcare to patients without rotating functions.  Thiseventually enhanced the continuation of patient care.Knowledge and understanding during the documentationprocess were promoted to establish a user-friendly andappropriate discharge form for discharge planning, aswell as for drawing references from patientsû information.Work - flow charts for hospital discharge and continuingcare were developed for all personnel working in theunit.  The effectiveness of the nursesû shift rotationswas also promoted to enhance communication withinthe interdisciplinary health care team and between healthcare providers and clients.  Significant patientinformation was discussed to encourage cooperationwithin the interdisciplinary team as well as to increasepatientsû and familiesû participation in discharge planning.  After these interventions were implemented,the length of hospital stay for elderly patients withchronic illnesses was shortened by an average of oneday and 88.2 per cent of the patients and their familieswere prepared and ready to return home by the time ofdischarge.  Almost all patients (95.75%) receiveddischarge and continuing care planning.  The levels ofpatient care satisfaction for most patients (73.3%) roseto a çhighé level.  Most importantly, all patients whowere the hospitalûs gold card members were referred totheir respective PCU for continuing care.